Evaluation of Limb Alignment, Component Positioning, and Function in Primary Total Knee Arthroplasty Using a Pinless Navigation Technique Compared with Conventional Methods - Keyes, Brian J.; Markel, David C.; Meneghini, Robert Michael (The Journal of Knee Surgery, 2013)
The purpose of this study was to examine component positioning, limb alignment, and the early functional range of motion of a pinless image-free computer-assisted navigation system, and compare it to conventional intramedullary component alignment methods. A total of 72 patients underwent cemented total knee arthroplasty. The pinless navigation group consisted of 40 knees in 39 patients, while the conventional group comprised 33 knees in 33 patients. Preoperative and postoperative radiographs were evaluated for coronal and sagittal alignment. Functional assessment was evaluated by early postoperative range of motion. There was no statistical significance when examining individual component alignment or early functional range of motion. When evaluating ability to achieve overall anatomic tibiofemoral alignment within a range of 4 to 7 degrees valgus, the conventional group was able to accomplish this 39% of the time, whereas the pinless navigation group succeeded in 65% of cases (p < 0.03). The tourniquet time was mean 59.5 minutes (range: 48 to 77 minutes) for the conventional group, compared with mean 71.9 minutes (range: 54 to 97 minutes) for the navigation group (p < 0.0001, 95% CI). The pinless navigation technique improved coronal anatomic alignment without complications that have been cited with use of femoral or tibial reference tracker pins or intramedullary alignment guides.
Keywords: computer-assisted; pinless; total knee arthroplasty; arthroplasty; navigation